Onychomadesis Following Hand-Foot Mouth disease Prospective Observational Study on 33 cases of Hand Foot Mouth Disease (World Journal of Current Medical and Pharmaceutical Research, 2020)
In 2019, an outbreak of hand, foot and mouth disease (HFMD)occurred in Maldives and many patients presented with onychomadesis following HFMD. Here we present a study of 33 cases out of which a total of 06 cases developed onychomadesis. Patients varied in clinical presentations ranging from mild to severe form of HFMD and during follow up 06 cases presented with peroidic shedding of nails involving both fingernails and toenails. All the patients were observed 4 to 6 weeks after diagnosis of HMFD was made. It was observed that onychomadesis developed was not related to the severity of the disease. Patients required only symptomatic treatment for HFMD and observation with assurance for onychomadesis as course was self-limited. Nail changes were temporary in nature and spontaneous regrowth occurred after shedding of the nails. Parental counselling played a cruicial role in management.